The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1089/dna.2015.3203
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Highly Upregulated in Liver Cancer Regulates the Tumor Necrosis Factor-α-Induced Apoptosis in Human Vascular Endothelial Cells

Abstract: Atherosclerosis is the major cause of myocardial infarction and stroke, which is a leading cause of morbidity and mortality in developed countries. During the pathological process of atherosclerosis, inflammation participates in all stages of atherosclerosis. Tumor necrosis factor-α (TNF-α), one of the most important inflammatory factor, induces apoptosis of endothelial cells, which play a central role in endothelial dysfunction. However, the underlying mechanism involved in long noncoding RNA (lncRNA) remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…Several recent studies have revealed that lncRNAs exert their biological functions partly through in trans or in cis modulation of the expression of nearby protein‐coding genes, providing an additional layer of modulation in molecular regulation . We therefore examined expression of LRP2BP in RP11‐714G18.1 overexpressing HUVECs and HA‐VSMCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have revealed that lncRNAs exert their biological functions partly through in trans or in cis modulation of the expression of nearby protein‐coding genes, providing an additional layer of modulation in molecular regulation . We therefore examined expression of LRP2BP in RP11‐714G18.1 overexpressing HUVECs and HA‐VSMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have revealed that lncRNAs exert their biological functions partly through in trans or in cis modulation of the expression of nearby protein-coding genes, providing an additional layer of modulation in molecular regulation. 7,8,18,19 We therefore examined expression of LRP2BP in RP11-714G18.1 overexpressing HUVECs and HA-VSMCs. As shown in Figure 2b and c, both mRNA and protein levels of LRP2BP were significantly enhanced by lentivirus-mediated overexpression of RP11-714G18.1 in either HA-VSMCs or HUVECs, suggesting that the expression of LRP2BP can be upregulated by RP11-714G18.1.…”
Section: Rp11-714g181 Promotes Expression Of Its Neighboring Proteinmentioning
confidence: 99%
“…It has been well-accepted that lncRNA function to the regulation of gene expression via acting as endogenous sponges for various miRNAs [12,23]. LncRNA HULC could posttranscriptionally sponge miR-186 [24], miR-122 [8], miR-372/miR-373 [25], and miR-9 [26], preventing target genes from degradation by these miRNAs, and thereby participating in a wide range of cellular process, like cell proliferation, differentiation, migration, invasion, apoptosis and inflammatory response. Herein, we found that lncRNA HULC was a molecular sponge for miR-124, that lncRNA HULC sequestrated miR-124, preventing MCL-1 from binding with miR-124.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…It is highly expressed in hepatocellular carcinoma and colorectal cancer with liver metastasis [14]. Since HULC expression has been shown during cancer growth and metastasis, it is a promising prognostic biomarker candidate for human cancers [15]. In recent years, HULC has been found to be dysregulated in osteosarcoma, pancreatic cancer, colorectal cancer, hepatocellular carcinoma, gastric cancer, hepatocellular carcinoma and large B-cell lymphoma [1622].…”
Section: Introductionmentioning
confidence: 99%